Fool me twice : [large type] a novel - Lindsay, Jeffry P. (Lindsay, Jeffry P. Riley Wolfe, 2020)
Stealing a Faberge egg. Surviving a double cross. And pulling off the most incredible robbery ever, for the world's most demanding, and dangerous collector. This will be the challenge of thief extraordinaire Riley Wolfe's life.